2005
DOI: 10.1093/pcp/pci170
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cell Division and Transcription by Cyclin-dependent Kinase-activating Kinases in Plants

Abstract: Cyclin-dependent protein kinases (CDKs) play key roles in the progression of the cell cycle in eukaryotes. A CDK-activating kinase (CAK) catalyzes the phosphorylation of CDKs to activate their enzyme activity; thus, it is involved in activation of cell proliferation. In plants, two distinct classes of CAK have been identified; CDKD is functionally related to vertebrate-type CAKs, while CDKF is a plant-specific CAK having unique enzymatic characteristics. Recently, CDKF was shown to phosphorylate and activate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 46 publications
2
70
0
5
Order By: Relevance
“…Two bootstrap consensus phylogenetic trees created by multiple alignment of yeast, Arabidopsis, and human CAK and CAKAK protein sequences using the COBALT algorithm indicated that CDKF;1 has higher homology to Kin28 and Mcs6 compared with members of the CDKD kinase family (see Supplemental Figures 2, 3A, and 3B online). Comparative analysis of functionally important kinase domains revealed that CDKF;1 contains an unusual insertion of 111 amino acids (Umeda et al, 1998(Umeda et al, , 2005 and changes in the structures of activation loop and substrate binding pocket (see Supplemental Figure 4 online), suggesting that CDKF;1 has some unique features compared with other CTD kinases.…”
Section: Position-specific Ser Phosphorylation Of Rnapii Ctd By the Amentioning
confidence: 99%
See 1 more Smart Citation
“…Two bootstrap consensus phylogenetic trees created by multiple alignment of yeast, Arabidopsis, and human CAK and CAKAK protein sequences using the COBALT algorithm indicated that CDKF;1 has higher homology to Kin28 and Mcs6 compared with members of the CDKD kinase family (see Supplemental Figures 2, 3A, and 3B online). Comparative analysis of functionally important kinase domains revealed that CDKF;1 contains an unusual insertion of 111 amino acids (Umeda et al, 1998(Umeda et al, , 2005 and changes in the structures of activation loop and substrate binding pocket (see Supplemental Figure 4 online), suggesting that CDKF;1 has some unique features compared with other CTD kinases.…”
Section: Position-specific Ser Phosphorylation Of Rnapii Ctd By the Amentioning
confidence: 99%
“…The Arabidopsis thaliana genome encodes three CAKs (CDKD;1/CAK3, CDKD;2/CAK4, and CDKD;3/CAK2), which are homologous to Kin28 and CDK7 and form different TFIIH-like complexes with cyclin-H;1, TFIIH-2, CAK assembly factor MAT1, and the putative CAK-activating kinase (CAKAK) CDKF;1/CAK1 (Shimotohno et al, 2004(Shimotohno et al, , 2006Van Leene et al, 2010). CDKF;1 appears to be specific to the plant kingdom and phosphorylates the T-loop of CDKD;2 and CDKD;3 in vitro (Shimotohno et al, 2004;Umeda et al, 2005). CDKD;1 and CDKD;3 are localized in nuclei, while CDKF;1 and CDKD;2 show both cytoplasmic and nuclear localization (Shimotohno et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As Arabidopsis kinases specific for the phosphorylation of Ser2 or Ser5 are not clearly established (Shimotohno et al, 2003;Umeda et al, 2005), we analyzed the effectiveness of selective kinase inhibitors as an alternative method of reducing Ser5P levels. Flavopiridol (Flap) or Seliciclib (Selic) can inhibit CDK7 and CDK9 in mammalian cells, which are predominantly responsible for phosphorylation of Ser5 and Ser2, respectively (Shapiro, 2006).…”
Section: Inhibition Of Ser5 Phosphorylation In Arabidopsismentioning
confidence: 99%
“…It therefore seems unique among metazoans and fungi [but see a review that describes a possibly similar situation in plants (Umeda et al, 2005)]. It appears rather perverse that the organism with the smallest genome and the most streamlined cell-cycle machinery should have the most CAKs.…”
Section: One Cak or Two: The Fission Yeast Variationmentioning
confidence: 99%